Monetary policy and redistribution: What can or cannot be neutralized with Mirrleesian taxes - Firouz Gahvari; Luca Micheletto (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper develops an overlapping-generations model with heterogeneous agents in terms of earning ability and cash-in-advance constraint. It shows that tax policy cannot fully replicate or neutralize the redistributive implications of monetary policy. While who gets the extra money becomes irrelevant, the rate of growth of money supply keeps its bite. A second lesson is that the Friedman rule is not in general optimal. The results are due to the existence of another source of heterogeneity among individuals besides differences in earning ability that underlies the Mirrleesian approach to optimal taxation. They hold even in the presence of a general income tax and preferences that are separable in labor supply and goods. If differences in earning ability were the only source of heterogeneity, the fiscal authority would be able to neutralize the effects of a change in the rate of monetary growth and a version of the Friedman rule becomes optimal.
Keywords: H21; E52; 330; monetary policy; fiscal policy; redistribution; Friedman rule; heterogeneity; overlapping generations; second best; Geldpolitik; Geldmengensteuerung; Verteilungswirkung; Steuerpolitik; Optimale Besteuerung; Second Best; Overlapping Generations